2024
DOI: 10.1038/s41598-024-54537-4
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary validation of the Mental Health Test in a psychiatric sample

Virág Zábó,
Dávid Erát,
Xenia Gonda
et al.

Abstract: To assist psychiatrists and clinical psychologists to assess their patients’ psychological immune competence-based capacities and resources, depending on the mental health disorder diagnosis and the severity of the symptoms, the present study examined the psychometric properties of the Mental Health Test in a psychiatric sample. The research was carried out in four Hungarian healthcare facilities using a cross-sectional design. A total of 331 patients (140 male, 188 female, and 3 who preferred not to disclose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The present study proposes a model for investigating the complex interrelationship between mental disorders, mental health competencies and well-being. Mental health competencies, as conceptualised in the Maintainable Positive Mental Health Theory 10 and included in the Mental Health Test 10 , 11 , have an important predictive value for well-being in the presence of psychopathological symptoms and/or mental disorders. In addition to their predictive value, mental health competencies are useful in other ways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study proposes a model for investigating the complex interrelationship between mental disorders, mental health competencies and well-being. Mental health competencies, as conceptualised in the Maintainable Positive Mental Health Theory 10 and included in the Mental Health Test 10 , 11 , have an important predictive value for well-being in the presence of psychopathological symptoms and/or mental disorders. In addition to their predictive value, mental health competencies are useful in other ways.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies based on Ryff’s model of psychological well-being 9 have found that purpose in life and personal growth are positively related to well-being, even in the presence of mental disorder symptoms. The identification and application of mental health competencies in psychiatric practice, particularly during the recovery phase, could serve as a new driving force, though the scientific understanding of their potential positive role in the context of mental disorders remains underexplored 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation